The greening of Kenya's banking sector: Macro-financial stability implications of a low carbon transition - Camilla C. Talam; Lucy Maru (Kenya Bankers Association (KBA), 2023)
Against the backdrop of climate-mitigation and green growth policies as well as regulations to account for climate-related risks in the financial sector, this study employs the Computable General Equilibrium model and Merton's Distance to Default model to study the implications of Kenya transitioning to a low carbon economy through introduction of a carbon tax on a carbon intensive sector. The study finds that a carbon tax would result in rise in general prices, and lower investment to GDP. These adverse effects are offset by a rise in real GDP and narrower fiscal and current account balances supported by a rise in government revenue and higher exports in low-carbon intensive sectors. A carbon tax policy would have adverse effects of declining output and income of firms in carbon intensive sectors. These adverse effects are varied which hedges the probability of default of a bank portfolio and allows for natural diversification to mitigate the adverse effects of such a policy for the banking sector. The carbon tax may also increase resilience in low carbon intensive firms where a bank may have exposures thus mitigating the environmental risks for these banks' exposures. From the findings, the paper persuades policymakers to consider a carbon tax rather than an emission trading system as a key carbon mitigation policy.
Keywords: 330; Green finance; Transition Risks; Carbon Pricing; Probability of Default